Due democratiche cristiane alla Consulta nazionale: Laura Bianchini e Angela Maria Guidi Cingolani - Rosanna Marsala (Laboratoire Italien)
This article is part of a broader study which seeks to reconstruct a female political tradition in order to ascertain some of the enduring reasons for the discrepancy between women’s formal and real access to decision-making. The ultimate goal is to highlight the role and contribution of women—especially those who have faded into oblivion—in the establishment of a democratic and republican Italy since they first participated in the National Consultative Assembly. The archives of the Chamber of Deputies and the Sturzo Institute, along with journal articles from the time, were the primary research sources.The Consulta was inaugurated on 25 September 1945 and, in a country where free assembly and public debate had not been the norm for some time, this represented the first step toward the reconstruction of democratic institutions. Convened by Parri’s government, the Consulta was chaired by Carlo Sforza, and included 13 women among its 430 members. Angela Cingolani Guidi (1896-1991) and Laura Bianchini (1903-1983) took part in it, representing the Christian Democrats. For them, as for the other members of the Consulta, it was a “political baptism” in institutions. Through an examination of the acts of the National Consulta and the press from the period, the paper explores the contribution of the above-mentioned members of the Consulta to debate on the issue of the reconstruction of the country and the affirmation of the new role of women both within institutions and the Party.